2013
DOI: 10.1002/fsn3.81
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of gelatin/multi‐walled carbon nanotube nanocomposite films as packaging materials

Abstract: Gelatin composite films were prepared from gelatin solutions (10% w/v) containing multi-walled carbon nanotubes (MWCNT, 0.5, 1, 1.5, and 2% w/w gelatin) as nanofiller. The water solubility, water swelling, water uptake, water vapor permeability (WVP), mechanical, and antibacterial properties of the films were examined. Water solubility, water swelling, water uptake, and WVP for gelatin films were 45 ± 1%, 821 ± 42%, 45 ± 1.1%, and 0.4 ± 0.022 g mm/m2 kPa h, respectively. Incorporation of MWCNT caused a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…It can be seen that the WVTR values of pure PU (PU-0) and PU-MWNTs composite films (PU-2, PU-3, and PU-5) were in the range of 404-732 g m -2 d -1 ( Table 2). Addition of MWNTs slightly decreased the WVTR values which could be due to the homogenous dispersion of MWNT aggregates in the polyurethane matrix and that blocked the water vapor transmission [24]. A study reported by Haider and co-workers (2007) was in accordance with our results whereby homogenous dispersion of MWNT aggregates in polymer matrix reduced water vapor transmission [27].…”
Section: Swelling Testsupporting
confidence: 92%
See 1 more Smart Citation
“…It can be seen that the WVTR values of pure PU (PU-0) and PU-MWNTs composite films (PU-2, PU-3, and PU-5) were in the range of 404-732 g m -2 d -1 ( Table 2). Addition of MWNTs slightly decreased the WVTR values which could be due to the homogenous dispersion of MWNT aggregates in the polyurethane matrix and that blocked the water vapor transmission [24]. A study reported by Haider and co-workers (2007) was in accordance with our results whereby homogenous dispersion of MWNT aggregates in polymer matrix reduced water vapor transmission [27].…”
Section: Swelling Testsupporting
confidence: 92%
“…Incorporation of MWNTs reduced swelling of the PU films possibly due to the increasing in hydrophobicity of the polyurethane matrix. This phenomenon possibly was due to the hydrophobic property of the MWNTs [23][24][25][26].…”
Section: Swelling Testmentioning
confidence: 99%
“…Gelatin-based nanocomposite films reinforced by low concentrations of MWCNTs can be synthesized in order to obtain improvements in water solubility, water swelling, water uptake, water vapor permeability (WVP), tensile strength, elongation at break, Young's modulus and antibacterial properties. These nanocomposite films can be used in food and biomedical applications as an alternative to conventional synthetic polymer [12].…”
Section: Introductionmentioning
confidence: 99%
“…These synthesized MWCNTs were used as nanofillers to develop the gelatin/MWCNT nanocomposite films. The water solubility, water swelling, oil swelling and antibacterial properties of these films were examined [12]. Garlic microparticles are synthesized using ball milling technique.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of multiwalled carbon nanotubes (MWNTs) slightly decreased the WVTR values which could be due to dispersion of MWNTs in the polyurethane matrix and blocked the water vapor transmission (Kavoosi et al 2014). However, these values still remain within the range of WVTR of commercial wound dressings values at 90-2893 g m −2 d −1 (Wu et al 1995).…”
Section: Swelling Ratio and Water Vapor Transmittance Rates (Wvtr)mentioning
confidence: 99%